RESISTANT ARTERIAL HYPERTENSION: IS THE CONSENSUS BETWEEN CONSERVATIVE AND INTERVENTIONAL THERAPY POSSIBLE? - Yu. I. Grinshtein; V. V. Shabalin (Столичная издательская компания, 2015)
Resistant hypertension is defined as hypertension uncontrolled with optimal doses of three antihypertensive agents, one of which is a diuretic. The up-to-date approaches to optimal pharmacologic and interventional treatment are discussed. Special emphasis is placed on some controversial aspects of new interventional procedures for resistant hypertension correction.